A Multimedia Analysis of Persuasion in the 2016 Presidential Election: Comparing the Unique and Complementary Effects of Political Comedy and Political Advertising. Issue 6 (2nd November 2018) - Warner, Benjamin R.; Jennings, Freddie J.; Bramlett, Josh C.; Coker, Calvin R.; Reed, Joel Lansing; Bolton, Joshua P.
Abstract : In this study, we test the indirect and conditional persuasive effects of a broadcast media echo chamber by combining political campaign attack ads with mockery and criticism on a late-night comedy program. A randomized experiment was conducted in which participants ( N = 559) were assigned to view one of four reconstructed episodes of Late Night with Seth Meyers : (a) anti-Trump comedy with anti-Trump campaign ads, (b) anti-Trump comedy with nonpolitical ads, (c) nonpolitical comedy with anti-Trump ads, and (d) nonpolitical comedy with nonpolitical ads. Results suggested that both comedy and ads exert persuasive effects on image perceptions of the candidates that subsequently influence vote intention. Furthermore, effects were largely confined to those who were high in need for cognition. There was no additive benefit to pairing ads with political comedy. The results are discussed regarding their contribution to theories of persuasion and information processing when applied to political comedy and political ads.